The Role of Accounting Information System Afflication In Reliability Financial Reporting - lesi Hertati; Otniel Safkaur; Dwi Yanti; Irlan Fery; Peny Cahaya Azwardi (Yayasan Ilomata, 2021)
The manifestation of regional financial autonomy can be seen in the regional financial accounting information system as a good government system characterized by increasingly low problems so that the information generated by the central government and regional governments in Indonesia is a form of quality financial reporting and effective application of accounting systems by various government agencies in Indonesia. Indonesia. This study aims to find out how the successful application of accounting information systems on financial reporting performance was produced. This study uses causality and population verification methods in this study are the district and city governments in the provinces of Papua and West Papua. The sampling technique uses a census so that all members of the population become research samples. The results of this study show empirical evidence that the successful application of accounting information systems and financial reporting performance is transparent and accountable.